Trade Facilitation in the Caribbean : The Case of Customs Performance - Ossio, Jose Eduardo Gutierrez; Alessandro, Martin; Neyra, Juan Jose (World Bank, Washington, DC, 2014)
The trade of goods and services and the inflows from Foreign Direct Investments (FDI) represent large proportions of their Gross Domestic Products (GDP), especially in English Speaking Caribbean (ESC) countries. Therefore, the proper functioning of the channels that connect them to the rest of the world, including customs offices, is essential to the performance of their economies. This note shows that, despite integration into the world economy, customs performance in the Caribbean countries is comparatively low. This note presents data from the Customs Assessment Trade Toolkit (CATT), which provides empirical evidence that processes do not meet adequate standards in terms of speed, predictability and transparency. This inconsistency is partially explained by the lack of an effective complementarity between the use of Information and Communication Technologies (ICT) systems and the actual operational practices. This policy note is organized as follows: section three presents evidence on the economic profile of the Caribbean countries to show high integration to the world economy. Trade and FDI are they key aspects being considered in this regard. Section four discusses the role of customs systems for economic development. It analyzes the performance of the Caribbean customs offices in a number of aspects (clearance times, predictability, and transparency) that the literature has identified as critical to promote competitiveness and development. Section five expands this analysis by focusing on how the use of ICT can improve customs performance in those aspects. Section six summarizes the lessons learned by the analysis of these data. Finally, the conclusions section presents some policy recommendations to deal with the inconsistency between high economic openness and low customs performance in the Caribbean countries.